Analisis Kelayakan Studi Pada Proyek Pembangunan Ruko Di Batam (Studi Kasus Pada Pembangunan Ruko Papa Mama Residence) - Hariyanto; Astutik, Yayuk Setyaning; Saputra, Ade Jaya (aspal, 2023)
The analysis of the feasibility study is the first step for investors to get an idea of the project that will be implemented. The final stage of this analysis would determine whether the project is feasible or not. The initial stage was the data collection stage that the author needed to simplify the analysis process. Additionally, the site plan, image data, and budget estimate plan were required. The researcher then analyzed using four methods, namely the Internal Rate of Return (IRR) dan Profitability Index (PI), Payback Period (PP), Net Present Value (NPV). The conclusion was drawn from the analysis result that the development project Ruko Papa Mama Residence was deemed feasible for implementation. With the estimated return for 2 years, and the results obtained from the IRR showed the number 28.2%, NPV is Positif ,as for the PI it showed the number 1.38 which is above 1. The projected net profit is Rp. 9,631,370,622. Therefore, the project is feasible to implement.